Water temperature as a quality factor in the use of streams and reservoirs - Ward, John Clayton, 1934-, author; Environmental Resources Center, Colorado State University, publisher (Colorado State University. Libraries, 1971)
Report consists of abstracts of eleven papers by John C. Ward (and others) whose research was primarily sponsored by the Office of Water Resources Research.
Submitted to Office of Water Resources Research, U.S. Department of Interior.
CER71-72JCW18.
Keywords: Thermal pollution of rivers, lakes, etc. -- Abstracts; Water temperature -- Abstracts